Extended network and algorithm finding maximal flows - Tran Ngoc Viet; Le Hong Dung (Institute of Advanced Engineering and Science, 2020)
Graph is a powerful mathematical tool applied in many fields as transportation, communication, informatics, economy, In ordinary graph the weights of edges and vertexes are considered independently where the length of a path is the sum of weights of the edges and the vertexes on this path. However, in many practical problems, weights at a vertex are not the same for all paths passing this vertex, but depend on coming and leaving edges. The paper develops a model of extended network that can be applied to modelling many practical problems more exactly and effectively. The main contribution of this paper is algorithm finding maximal flows on extended networks.